Optimalisasi Pengelolaan Zakat Produktif dalam Perspektif Hukum Ekonomi Syariah dan Peraturan Perundang-undangan di Indonesia - Hamidah Azzahra (Al Itmamiy Jurnal Hukum Ekonomi Syariah (Muamalah), 2025)
Productive zakat is a form of zakat distribution that is aimed at increasing the independence of mustahik through sustainable business development. In the context of sharia economic law, productive zakat is considered capable of encouraging the achievement of social justice and economic empowerment of the community if managed in accordance with sharia principles and laws and regulations. This article aims to analyze the implementation of productive zakat in Indonesia from the perspective of sharia economic law and to evaluate the suitability of its implementation with applicable regulations. The study uses a normative juridical method with a conceptual approach and a comparison between the theory of zakat fiqh and the practice of zakat institutions. Data were collected through literature reviews, documentation studies, and analysis of DSN-MUI Fatwa No. 190/2023 and Law No. 23 of 2011 concerning Zakat Management. The results of the study show that the implementation of productive zakat still faces challenges, especially in the aspects of accountability, selection of targeted mustahik, and business sustainability after capital provision. From the perspective of sharia economic law, zakat management must uphold the principles of maslahat, justice, and amanah. Therefore, an integrated productive zakat governance model is needed between sharia principles, modern management, and a transparent reporting system. In conclusion, optimizing productive zakat requires synergy between zakat institutions, regulators, academics, and the community in order to realize the function of zakat as an instrument for the development of the people's economy.